THE INFLUENCE OF MARKETING STRATEGY AND SERVICE INNOVATION ON THE GROWTH OF PRIVATE HOSPITAL PATIENTS - Tia Ariani Salsabila; Kosasih; Vip Paramarta; Farida Yuliaty; Fitriana (RADJA PUBLIKA, 2025)
Private hospitals need to implement marketing strategies and service innovation to increase the number of patients and maintain a competitive advantage. Marketing strategies increase public awareness, while service innovation improves quality and patient satisfaction. This research aims to analyze the influence of both. The method used is a literature study with secondary data from articles and literature taken from Google Scholar (2020-2024). The results of research conducted by several authors also show that marketing strategies and service innovation have a significant impact in increasing the number of patients visiting the hospital.The research results show that these two factors have a positive effect on the number of patient visits. Effective marketing strategies can attract public interest in health services, while service innovation improves the quality of the patient experience. These two factors interact, helping hospitals strengthen their competitive advantage and drive patient growth. Therefore, hospitals must develop effective marketing and service innovation strategies to maintain growth and competitive advantage.